2012
DOI: 10.1097/nmd.0b013e31825322b3
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of Barriers to Care for Trauma-Related Mental Health Problems Among Low-Income Minorities in Primary Care

Abstract: This study aimed to identify barriers and facilitators of mental health care for patients with trauma histories via qualitative methods with clinicians and administrators from primary care clinics for the underserved. Individual interviews were conducted, followed by a combined focus group with administrators from three jurisdictions; there were three focus groups with clinicians from each clinic system. Common themes were identified, and responses from groups were compared. Administrators and clinicians repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[12][13][14][15] Medical clinicians are less likely to screen for trauma-related mental health issues because they overestimate the time it takes, and they have poor access to appropriate services and treatment. 12,16 Early detection and intervention could decrease the likelihood of the assorted problems associated with childhood trauma exposure, such as mental health disorders, chronic medical conditions, and adult health risk behaviors. 17 Early detection could also decrease the likelihood of revictimization, 18 and improve overall health, which can positively influence quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Medical clinicians are less likely to screen for trauma-related mental health issues because they overestimate the time it takes, and they have poor access to appropriate services and treatment. 12,16 Early detection and intervention could decrease the likelihood of the assorted problems associated with childhood trauma exposure, such as mental health disorders, chronic medical conditions, and adult health risk behaviors. 17 Early detection could also decrease the likelihood of revictimization, 18 and improve overall health, which can positively influence quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, clinicians and administrators observed stigma-related patient resistance, symptom-related difficulties such as planning or denial, transportation limitations, and financial barriers to patient participation in a mental health care plan (Chung et al, 2012;Mesidor et al, 2011). However, systemic and service delivery issues also serve as obstacles to consumers' ability to utilize mental health services.…”
Section: Factors Influencing Use Of Mental Health Servicesmentioning
confidence: 99%
“…However, systemic and service delivery issues also serve as obstacles to consumers' ability to utilize mental health services. Chung et al (2012) found that provider referral options, reimbursement issues, and education constrained primary care providers' ability to appropriately assist patients with their mental health care needs. After interviewing providers in a mental health care setting, Mesidor et al (2011) reported that mental health budget cuts and provider competency influence an organization's ability to meet comprehensive patient needs.…”
Section: Factors Influencing Use Of Mental Health Servicesmentioning
confidence: 99%
See 2 more Smart Citations